Efficacy and Safety of Anti-Xa-Guided Versus Fixed Dosing of Low Molecular Weight Heparin for Prevention of Venous Thromboembolism in Trauma Patients: A Systematic Review and Meta-Analysis. Issue 5 (22nd May 2023) - Tran, Alexandre; Fernando, Shannon M.; Gates, Rebecca S.; Gillen, Jacob R.; Droege, Molly E.; Carrier, Marc; Inaba, Kenji; Haut, Elliott R.; Cotton, Bryan; Teichman, Amanda; Engels, Paul T.; Patel, Rakesh V.; et al.
Abstract : Purpose: Trauma patients are at high risk of venous thromboembolism (VTE). We summarize the comparative efficacy and safety of anti-Xa-guided versus fixed dosing for low molecular weight heparin (LMWH) for the prevention of VTE in adult trauma patients. Methods: We searched Medline and Embase from inception through June 1, 2022. We included randomized controlled trials or observational studies comparing anti-Xa-guided versus fixed dosing of LMWH for thromboprophylaxis in adult trauma patients. We incorporated primary data from 2 large observational cohorts. We pooled effect estimates using a random-effects model. We assessed risk of bias using the ROBINS-I tool for observational studies and assessed certainty of findings using GRADE methodology. Results: We included 15 observational studies involving 10, 348 patients. No randomized controlled trials were identified. determined that, compared to fixed LMWH dosing, anti-Xa-guided dosing may reduce deep vein thrombosis [adjusted odds ratio (aOR); 0.52, 95% CI: 0.40–0.69], pulmonary embolism (aOR: 0.48, 95% CI: 0.30–0.78) or any VTE (aOR: 0.54, 95% CI: 0.42–0.69), though all estimates are based on low certainty evidence. There was an uncertain effect on mortality (aOR: 1.06, 95% CI: 0.85–1.32) and bleeding events (aOR: 0.84, 95% CI: 0.50–1.39), limited by serious imprecision. We used several sensitivity and subgroup analyses to confirm the validity of our assumptions. Conclusion: Anti-Xa-guided dosing may be more effective than fixed dosing for prevention of deep vein thrombosis, pulmonary embolism, and VTE for adult trauma patients. These promising findings justify the need for a high-quality randomized study with the potential to deliver practice changing results.